KOMUNIKASI INTERPERSONAL ANAK BROKEN HOME PASCA PERCERAIAN ORANG TUA (Studi Fenomenologi di Kecamatan Kuningan Kabupaten Kuningan) - Rifqi Fauzi (Jurnal Bimbingan Penyuluhan Islam, 2020)
The purpose of this study was to determine interpersonal communication in broken home families and the development of broken home children after the divorce of parents that occurred in Kuningan District, Kuningan District. This study uses a qualitative method with a phenomenological approach. The data collection techniques are used through observation, in-depth interviews, and documentation studies. The data analysis technique used in this study was a qualitative descriptive analysis technique. While the data validity test is checked using source triangulation techniques. The results of this study indicate that interpersonal communication in broken home harmonious families runs well for their children by giving each other attention and communication smoothly making moral development and personality development of children to be controlled and fine for children's lives while broken home families are not harmonious interpersonal communication is not going well so that the child's development in both morals and personality changes considerably unlike other normal children who are triggered due to lack of communication and attention from parents. Suggestion from this research is that in any condition and no matter how busy parents must keep aside their time for their children both by communicating and interacting directly.